Evaluation of Quality of Life in Adult Celiac Patients Living in Lithuania and Their Compliance with a Gluten-Free Diet: A Pilot Study - Yeliz Serin; Jurgita Andruškienė; Anil K. Verma; Monika Śmiełowska; Nerijus Dzingelevičius; Albinas Vilčiauskis; Rita Vaičekauskaitė; Vijolė Bradauskienė; Bogusław Buszewski; Reda Dzingelevičienė (Medicina)
Background and Objectives: Celiac disease (CD) is a common gluten-related disorder associated with significantly worsened quality of life. The aim of this pilot study was to evaluate the quality of life of adult celiac patients living in Lithuania and their compliance with a gluten-free diet. Materials and Methods: This cross-sectional study was conducted on individuals aged 18 to 75 years diagnosed with CD and residing within the borders of Lithuania. This pilot study involved 73 participants, comprising 68 females and 5 males. The CD Specific Quality of Life Scale (CD-QOL) consisted of 20 items across four sub-dimensions. Responses to scale items were graded with a score ranging from 1 (not at all) to 5 (very much). The total score obtained from the scale can range up to 100, with a score < 40 classified as poor, 40–50 as moderate, and > 50 as good quality of life. Additionally, ten questions related to gluten-free diet-related quality of life were used. Results: The mean age of diagnosis for females (32.6 ± 11.7) was higher than that for males (22.0 ± 12.1), p < 0.05. The mean self-reported BMI for males (25.8 ± 4.5) was higher than that for females (22.3 ± 5.2), p < 0.05. The mean quality-of-life score (66.4 ± 12.5) was significantly higher in the good quality-of-life group compared to the poor group (33.7 ± 3.9), p < 0.001. Half of the respondents (50.7%) reported that gluten-free products are expensive, and 45.2% confirmed difficulties in dining out on a gluten-free diet. Conclusions: The results of this pilot study indicate that CD is associated with a worsened quality of life and that compliance with a gluten-free diet is primarily influenced by economic factors, such as the high cost of the diet.